Supporting access and equity to mathematics in low-SES contexts: A Systematic Literature Review - Bray, Aibhin (My University, 2026)
Disparities in achievement and equity associated with socio-economic status (SES) are particularly pronounced in mathematics. Research highlights that students from low-SES backgrounds often experience less effective instruction and lower teacher expectations. Factors such as ability grouping and school environment significantly impact attitudes and performance in mathematics, with low-SES students tending to experience higher anxiety and lower self-concept than their more advantaged peers. International studies show that the relationship between achievement and socio-economic status varies across countries, suggesting that with appropriate support, overcoming a disadvantaged background is possible; how this can be realised by interventions is less clear; questions remain about what forms of support effectively promote equity, and under what conditions. This review contributes by exploring evidence-based research that aims to support students’ access to mathematics. It explores how the interventions engage with complex contextual factors and reflects the forms of inequity they might disrupt. The analysis focuses on 29 empirical studies and is guided by Bronfenbrenner’s Process-Person-Context-Time (PPCT) model and Enchikova et al.’s conceptualisation of Equity. Key findings emphasise the importance of pedagogies that support low-SES students’ sense of relevance of the subject, impacting their attitudes and motivation. Adequate resources (tangible and intangible), and supportive environments reflecting high expectations are essential. Timing is key, with lower-secondary school reflecting an important inflection point. Perhaps most importantly, recognition of the centrality of the teacher, with sustained support, professional development and common planning time, is crucial to the development of the kinds of teaching and learning environments conducive to students’ access and equity in mathematics.
PUBLISHED
Keywords: Mathematics education; lower secondary; low-SES; educational disadvantage; systematic literature review; Inclusive Society; EDUCATION; Inclusive Education; Mathematics Education